Relative peer quality and firm performance - Bill Francis; Iftekhar Hasan; Sureshbabu Mani; Pengfei Ye (Bank of Finland, 2016)
​This study examines the performance impact of the relative quality of a CEO's compensation peers (peers selected to determine a CEO's overall compensation) and bonus peers (peers selected to determine a CEO's relative-performance-based bonus). We use the fraction of peers with greater managerial ability scores (Demerjian, Lev, and McVay, 2012) than the reporting firm to measure this CEO's relative peer quality (RPQ). We find that firms with higher RPQ tend to earn superior risk-adjusted stock returns and experience higher profitability growth compared with firms that have lower RPQ. These results cannot be fully explained by a CEO's power, compensation level, intrinsic talent, nor by the board's possible motivation to use peers to signal a firm's prospect. Learning among peers and the increased incentive to work harder induced by the peer-based tournament, however, might contribute to RPQ's positive performance effect. Preliminary evidence also shows that high RPQ is not associated with increased earnings management or increased risk-taking behaviors.
URN:NBN:fi:bof-201604121080
Keywords: G30; 330